Swimming and rafting of E.coli microcolonies at air–liquid interfaces. Issue 1 (22nd October 2017) - Sinibaldi, Giorgia; Iebba, Valerio; Chinappi, Mauro
Abstract: The dynamics of swimming microorganisms is strongly affected by solid‐liquid and air‐liquid interfaces. In this paper, we characterize the motion of both single bacteria and microcolonies at an air‐liquid interface. Both of them follow circular trajectories. Single bacteria preferentially show a counter‐clockwise motion, in agreement with previous experimental and theoretical findings. Instead, no preferential rotation direction is observed for microcolonies suggesting that their motion is due to a different physical mechanism. We propose a simple mechanical model where the microcolonies move like rafts constrained to the air‐liquid interface. Finally, we observed that the microcolony growth is due to the aggregation of colliding single‐swimmers, suggesting that the microcolony formation resembles a condensation process where the first nucleus originates by the collision between two single‐swimmers. Implications of microcolony splitting and aggregation on biofilm growth and dispersion at air‐liquid interface are discussed. Abstract : We analyzed the motion of single E. coli and microcolonies at air–liquid interface. Our experimental data show that both single swimmers and microcolonies follow circular trajectories. Single bacteria preferentially show a counterclockwise motion, while no preferential rotation direction is observed for microcolonies. We explained these behaviors via a simple mechanical model where the microcolonies move like rafts constrained to the air–liquid interface. In addition, microcolonies trapped at air–liquid interface can easily undergo to splitting and aggregation phenomena.